Cancellation of elective surgery and associated factors among patients scheduled for elective surgeries in public hospitals in Harari regional state, Eastern Ethiopia - Adugna, Damte; Worku, Teshager; Hiko, Ahmed; Dheresa, Merga; Letta, Shiferaw; Sertsu, Addisu; Kibret, Haregeweyn (Frontiers in Medicine, 2023)
Abstract Background: Cancelling elective surgeries are a significant problem in many hospitals; which leads to patient dissatisfaction, increased costs, and emotional trauma for patients and their families. Despite this, there is limited information about the cancellation of elective surgeries in Ethiopia, mainly in the study area. Objective: The aim of this study was to assess the magnitude of cancellation and associated factors among patients scheduled for elective surgeries in public hospitals in the Harari Region, Eastern Ethiopia, from August 1to August 30, 2021. Methods: A hospital-based cross-sectional study was conducted on 378 patients scheduled for elective surgery. Data were gathered using a non-random sequential sampling approach. A structured face-to-face interviewer-administered questionnaire was employed. The gathered information was input into Epidata version 3.1, and then it was exported to Statistical Package for Social Software version 26. To find the variables linked to the postponement of elective surgery, binary and multiple logistic regression analyses were conducted. In the binary analysis, all variables with a p-value of less than 0.25 were included in the multivariable analysis. Finally, a 0.05 p-value with a 95% confidence interval and an adjusted odds ratio was used to confirm significance. Results: Of the 378 patients who were planned to have elective surgery and were part of the research, 133 (35.2%) had their procedure canceled (confidence interval: 29.4–39.6). Being female sex (adjusted odds ratio: 2.46; 95% confidence interval: 1.44-4.203), lack of formal education (adjusted odds ratio: 2.03; 95% confidence interval: 1.15-3.58), place of residence (adjusted odds ratio: 1.70; 95% confidence interval: 1.03-2.81), increase in blood pressure (adjusted odds ratio: 5.09; 95% confidence interval:1.90-13.59), and ophthalmologic surgery (adjusted odds ratio: 3.76; 95% confidence interval:1.41-10.0) were factors associated to cancellation of elective surgery. Conclusions: In analysis of this study, nearly one-third of patients scheduled elective surgical operations were postponed. The primary contributing variables to the cancellation of surgery were being a female, lack of formal education, place of residence, ophthalmologic surgery and increase in blood pressure. Therefore, timely evidence-based reporting through the supervision team was advised to decrease cancellation. Keywords: Cancellation, Elective surgery, Operation theatre, Harar, Ethiopia